Entrepreneurial Marketing dan Jejaring Sosial dalam Usaha Kecil: Studi Kasus tentang Bisnis Petshop di Kabupaten Bandung - Jajang Ginanjar; Margo Purnomo; Erna Maulina (Organum: Jurnal Saintifik Manajemen dan Akuntansi, 2021)
This article aims to examine how small entrepreneurs use social networks to develop and implement marketing strategies. The type of small business studied is the Petshop business. The research method used is qualitative by conducting in-depth interviews and analysis with Petshop entrepreneurs through an entrepreneurial marketing perspective. Ultimately, we found that Petshop entrepreneurs are using social connections through market intelligence, new customer acquisition, and current customer retention to create and deliver more value to customers. Entrepreneurs take steps to build emotional attachments and carry out marketing activities through giving gifts or by approaching customers through the community, and most of the entrepreneurs in the Petshop business in Bandung Regency do marketing through physical (offline) stores and online shops. The majority of entrepreneurs stated that the application of the entrepreneurial marketing concept and strengthening social networks were important in the continuity of the Petshop business, only one Petshop entrepreneur had contradictory statements, especially in the aspect of searching for market information.